A history of South African (SA) Psychology - Nicholas, Lionel; Psychology Graduate Assistant School of Health Sciences Monash South Africa (2014)
This historical account of SA psychology spans over hundred years of its engagement with international psychology and the influence of racism on its development. It traces Jan C. Smuts’s correspondence with Adler, Koffka and Perls and Allport’s extensive contact with SA psychologists. The positive impact of the academic boycott in turning psychology towards the concerns of the oppressed is delineated, as well as the response of professional organizations to apartheid. The extensive reciprocal visits of US and Dutch phenomenologists are described and the contributions of Wolpe, Rachman and Lazarus to behavior therapy are noted.